(untitled) (LACCEI, 2024)
The objective of this paper is to analyze innovation and entrepreneurship as drivers of economic growth in Colombia from a reflective perspective. Considering the challenges of the international competitive environment, a theoretical recognition of concepts and associated systems was made, and a systematized review of articles, theses and research associated with the topic addressed was carried out. The theoretical review revealed that Colombia is lagging in its levels of competitiveness and economic growth compared to other countries whose economies are based on knowledge, which is reflected in slow growth and low employability of companies. It was concluded that the creation of an enabling environment for innovation and entrepreneurship requires clear and credible laws and policies, accessible investments and guarantees, support and opportunities for all, and additionally the promotion of competition and research.